2009
DOI: 10.1590/s0102-311x2009000900004
|View full text |Cite
|
Sign up to set email alerts
|

Uso regular de serviços odontológicos entre adultos: padrões de utilização e tipos de serviços

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
1
60

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(113 citation statements)
references
References 29 publications
8
44
1
60
Order By: Relevance
“…Camargo et al 4 (2009) and Matos et al 10 (2001) found prevalences of regular visits of 32.8% and 24.6% respectively, similar to the present study. This is likely due to the similarities in the educational level of the samples, since greater education is associated with utilization.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Camargo et al 4 (2009) and Matos et al 10 (2001) found prevalences of regular visits of 32.8% and 24.6% respectively, similar to the present study. This is likely due to the similarities in the educational level of the samples, since greater education is associated with utilization.…”
Section: Discussionsupporting
confidence: 90%
“…1,4,10 In contrast to Matos et al 10 (2001) and in agreement with Camargo et al 4 (2009), the self-perception of a need for treatment was measured in four levels by the present study. Those that responded "not having a needs because everything was fi ne" or that "yes, for a checkup" had higher prevalence of regular use compared to individuals that said "despite having a problem to resolve, they could wait".…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations